Comparative botanical and phytochemical evaluation of Calotropis procera Linn. and Calotropis gigantea Linn. Root - Sharad Srivastava, Adarsh Pratap Singh, A. K. S. Rawat (Journal of Applied Pharmaceutical Science, 2015)
The present study aimed to develop pharmacognostical and phytochemical descriptors (HPTLC) of Calotropis procera and Calotropis gigantea. β-sitosterol which is one of the common terpene content and a potent antioxidant, purgative, antispasmodic and expectorant, has also been studied through a simple and high-precision method using high performance thin layer chromatography (HPTLC). This may be utilized by pharmaceutical industries for quality evaluation, ensuring successful commercial exploitation of this drug. From the present study it has been observed that both Calotropis procera and C. gigantea have similar microscopic characteristics, physico-chemical parameters showed a little variation as total ash components and extractive values are little less in C. gigantea. HPTLC studies also showed similar qualitative profile with some quantitative variations in total β-sitosterol, which was higher in C. gigantea (2.79%).
Keywords: Pharmacognosy, HPTLC, Calotropis procera, Calotropis gigantea.